Evaluation of Potato Genotypes for Plant and Yield Traits at Dailekh District, Nepal - Luitel, Binod Prasad; Thapa, Bihani; Bhandari, Bishnu Bahadur (Agriculture Development Journal, 2022)
Field experiments were conducted at on-farm condition of Dailekh during the spring season for two years (2019 and 2020) to study the plant and yield traits of potato genotypes, and to select high yielding and farmers' preferred genotype. Five promising potato genotypes (PRP226567.2, CIP395017.242, PRP136769.1, PRP276264.1 and CIP393617.1) were studied for their plant and yield traits and compared them with 'Kufri Jyoti', a popular check variety. Experiments were laid-out in randomized complete block design (RCBD) with four replications. Results showed that genotypes exhibited significant differences in all the plant and yield characters. CIP395017.242 gave the highest marketable (23.5 t/ha) and total tuber yield (25.9 t/ha). As compared to Kufri Jyoti, CIP395017.242 gave 12.4% higher marketable tuber yield. Farmer's preferences on plant and tuber of CIP395017.242 were also similar to Kufri Jyoti. Therefore, genotype CIP395017.242 can be recommended to grow at on-farm condition of Dailekh.